Kontribusikepemimpinankepalasekolah Komitmen Dan Efektifitas Organisasi Terhadap Kinerja Pengurus Bursakerja Khusus (BKK) SMK Se Kabupaten Klaten - Paryanti, Yeni; , Dr. Sumardi, M.Si; , Dr. Suyatmini, M.Si (2017)
The aims of this study was to determine : 1) the contribution of principal's leadership, organizational commitment, organizational effectiveness to BKK performance managemen. 2) the contribution of principal's leadership to the BKK performance management 3) the contribution of organizational commitment to the BKK performance managememt 4) the contribution of organizational efffectiveness to the BKK performance management. The study was quantitative descriptive study. The population of the study management BKK of State Vocational High School in Klaten regency. Sampling by using stratified random sampling profortional. The research instrument that uses a Likert questionnaire models have been tested for validity and reliability, and analyzed by correlation and regression techniques.The result of the data analysis showed (1) there is positive and very significant contribution of the principal's leadership, organizational commitment, organizational effectiveness to BKK performance managemen with the percentage 85,425 %. (2) there is positive and very significant contribution of the principal's leadership to BKK performance managemen with the percentage 33,167 %, (3) there is positive and very significant contribution of the organizational commitment to BKK performance managemen with the percentage 14,368 %, (4) there is positive and very significant contribution of the organizational effectiveness to BKK performance managemen with the percentage 37,890 %